REABILITY OF MANUAL MUSCLE TEST EXAMINATION OF STROKE PATIENT IN SARDJITO HOSPITAL - , MUHD SHAHRULNIZAM BIN IZANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Muscle testing is the evaluation of contractile units, including muscles and tendons, and their ability to generate forces. Muscle testing is indicated in any individual with suspected or actual impaired muscle performance, including strength, power, or endurance. The effects of a stroke depend on several factors, including the location of the obstruction and how much brain tissue is affected. The stroke occurred: the right hemisphere, the left hemisphere, the cerebellum or the brain stem. The chain of nerve cells that runs from the brain through the spinal cord out to the muscle is called the motor pathway. Normal muscle function requires intact connections all along this motor pathway. Damage at any point reduces the brain's ability to control the muscle's movements. This reduced efficiency causes weakness, also called paresis.The role of the muscle system in spinal function has become increasingly well acknowledged. This study will present the validity and reliability of Manual Muscle Test (MMT) as evaluation tool for the assessment of musculoskeletal muscle weakness in stroke patients and it will be analyzed using Cronbachâs Alpha. This study will be held in RSUP Dr. Sardjito. Objective: The main objective of this study is to determine the validity and reliability of Manual Muscle Test in stroke patients of RSUP Sardjito. Method: This is an experimental research